Partner notification and STI patient experiences in Ekurhuleni East, Gauteng, South Africa - Noluthando Mpobole; Raikane J. Seretlo; Mathildah M. Mokgatle (African Journal of Primary Health Care & Family Medicine, 2025)
Background: Sexually transmitted infections (STIs) are a widespread public health concern, disproportionately impacting young adults. This group is at higher risk due to factors like limited knowledge, misconceptions about sexual health, inconsistent condom use, multiple sexual partners, and barriers to youth-friendly sexual and reproductive health services. Partner notification (PN) strategies are critical in STI control. Effective notification and communication with sexual partners can help break the infection chain and encourage early diagnosis and treatment. However, the dynamics of PN in young individuals remain unclear.